THE EFFECT OF 70% ETHANOL OF STRAWBERRIES (Fragaria x ananassa) IN FACIAL SPRAY GEL PREPARATIONS ON PHYSICAL PROPERTIES, PHYSICAL STABILITY AND ANTIOXIDANT ACTIVITY - Diana Arnandea (INDONESIA NATURAL RESEARCH PHARMACEUTICAL JOURNAL, 2020)
Strawberry fruit (Fragaria x ananassa) is a plant that comes from the Rosaideae family which has a high secondary metabolite content, one of which is rich in anthocyanin pigment which has high antioxidant properties, which can make the skin bright, clean, smooth and can prevent premature aging. This study aims to determine the effect of different concentrations of 70% ethanol extract of strawberries (Fragaria x ananassa) in the preparation of preparations and evaluation of facial spray gel preparations and antioxidant activity. To obtain a facial spray gel that has good stability, the research stages were carried out starting from the formulation, evaluation of the facial spray gel preparation and the antioxidant activity test of strawberries (Fragaria x ananassa). The formulation made consisted of four formulas namely F1, F2, F3, F4 formula with 70% ethanol extract concentration variation of strawberries (Fragaria x ananassa). Data analysis for the antioxidant yield of 70% ethanol extract and the results of physical properties were processed using linear regression while for stability testing using SPSS 24 applications. The highest antioxidant activity results were found in F4 which has the highest IC50 value of 33.0132 ppm in physical properties test showed increasingly high ethanol extract of 70% strawberries (Fragaria x ananassa) in the formula will increase the adhesion and viscosity test while in the pH test, pump delivery, spraying pattern decreases. In the stability testing of facial spray gel at room temperature (25-27oC) storage, both F1, F2, F3 and F4 were declared stable during storage except the pump delivery test was not stable at room temperature